Investigation of fluid flow through cellular structures - Sadir, Sahba (2010)
In this study, the cellular structures models of a porous medium containing a fluid flow phase within the pores or spaces of the solid matrix are investigated. A computational fluid dynamics of the three dimensional (3D) macro structures is developed from simple to complex model. Nine model variants are designed with different structure and geometry. To this end, the influence of cellular structure on the fluid flow, in terms of velocity, wall shear stress and pressure drop are investigated using the commercial FLUENT software. The acquired permeability values from obtained pressure drop and Darcy’s law are compared with permeability values calculated from Kazeny-Carman equation, there is a good agreement for permeability values for these two types of values which can validate the simulation.